2022
DOI: 10.1080/14756366.2022.2037579
|View full text |Cite
|
Sign up to set email alerts
|

Acipimox inhibits human carbonic anhydrases

Abstract: Acipimox, a nicotinic acid derivative in clinical use for the treatment of hyperlipidaemia, incorporates a free carboxylic acid and an N-oxide moiety, functionalities known to interact with the metalloenzyme carbonic anhydrase (CA, EC 4.2.1.1) and inhibit its activity. Herein we report that acipimox acts as a low micromolar CA inhibitor (CAI) against most human (h) isoforms possessing catalytic activity, hCA I – XIV. By using computational techniques (docking and molecular dynamics simulations), we propose tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…However, they may provide interesting hints for the drug design of novel CA VA inhibitors belonging to new chemotypes compared to the well known sulphonamides, sulfamates or phenol derivatives. Acipimox 39 , a nicotinic acid derivative in clinical use for the treatment of hyperlipidaemia ( Figure 6 ) was also reported recently 65 to act as low micromolar hCA VA/VB inhibitor. By using computational methods, the same study suggested that acipimox coordinates through its carboxylate moiety to the zinc ion from the CA active site 65 .…”
Section: Drug Design Of Ca Inhibitors As Antiobesity Agentsmentioning
confidence: 57%
See 1 more Smart Citation
“…However, they may provide interesting hints for the drug design of novel CA VA inhibitors belonging to new chemotypes compared to the well known sulphonamides, sulfamates or phenol derivatives. Acipimox 39 , a nicotinic acid derivative in clinical use for the treatment of hyperlipidaemia ( Figure 6 ) was also reported recently 65 to act as low micromolar hCA VA/VB inhibitor. By using computational methods, the same study suggested that acipimox coordinates through its carboxylate moiety to the zinc ion from the CA active site 65 .…”
Section: Drug Design Of Ca Inhibitors As Antiobesity Agentsmentioning
confidence: 57%
“…Acipimox 39 , a nicotinic acid derivative in clinical use for the treatment of hyperlipidaemia ( Figure 6 ) was also reported recently 65 to act as low micromolar hCA VA/VB inhibitor. By using computational methods, the same study suggested that acipimox coordinates through its carboxylate moiety to the zinc ion from the CA active site 65 .…”
Section: Drug Design Of Ca Inhibitors As Antiobesity Agentsmentioning
confidence: 57%
“…It inhibits VLDL synthesis, and consequently lowers plasma triglyceride levels while elevating highdensity lipoprotein (HDL). 108 Carbadox and olaquindox (Figure 8) are structural analogues of the natural products iodinin and myxin. They have been used as antimicrobial agents in veterinary medicine as feed additives to promote growth.…”
Section: Drugs Containing N-oxide Groupsmentioning
confidence: 99%
“…This leads to a reduction in the precursor pool size of the very low-density lipoprotein (VLDL)-triglyceride. It inhibits VLDL synthesis, and consequently lowers plasma triglyceride levels while elevating high-density lipoprotein (HDL) …”
Section: Drugs Containing N-oxide Groupsmentioning
confidence: 99%
“…The ubiquitous metalloenzymes carbonic anhydrases (CAs) [ 1 , 2 , 3 , 4 , 5 , 6 ] are present in bacteria [ 7 , 8 ] and fungi [ 9 , 10 , 11 , 12 ], plants and animals. Inhibitors of these enzymes have been clinically exploited for decades, and the discovery of multiple human isoforms [ 13 , 14 , 15 , 16 , 17 , 18 ] has led to many new applications and the development of new therapeutic principles, among them antiglaucoma [ 19 , 20 , 21 ] and antitumor drugs but also antiepileptic [ 22 , 23 , 24 , 25 , 26 ] and antiobesity drugs [ 27 , 28 , 29 ] as well as agents for the management of Alzheimer’s disease [ 30 , 31 ], neuropathic pain, cerebral ischemia, and some forms of arthritis [ 32 , 33 , 34 ]. Furthermore, the development of inhibitors for bacterial carbonic anhydrases is thought as a new concept to develop antibacterial drugs [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%